Developer Ecosystems for Software Safety. - Kern, Christoph (Communications of the ACM, 2024)
This article sets out to improve upon the current state of design principles and implementation guidance for software safety and security by focusing on the developer's ecosystem to prevent software defects. The article emphasizes a continuous assurance method focusing on the implementation of safe coding and secure design for all applications and tools used by software developers.